The social construction of sexuality - Seidman, Steven (W.W. Norton & Company, 2015)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, Seidman delves into issues of social control that inform popular beliefs and moral standards. The new Third Edition features three new chapters that focus on the changing cultures of intimacy, the promise and perils of cyber intimacies, and youth struggles to negotiate independence and intimate solidarity.-- Provided by Publisher.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétérosexisme; intimité; premier cycle; privilèges; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; travail; travail du sexe

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Sexualités, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes